The impact of decentralization on socio-economic development; a case study of Ga-East Municipal Assembly. - Baah, Richard Asamoah (KNUST, 2025)
A Thesis Submitted In Partial Fulfillment Of The Requirements For The Degree Of Master In Public Administration.